Analisis Risiko Usahatani Padi Sawah Di Desa Radey Kecamatan Tenga Kabupaten Minahasa Selatan - Kesek, Theofany; Baroleh, Jenny; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2024)
The purpose of the study was to analyze the risk of wet-rice farming in Radey Village, Tenga Subdistrict, South Minahasa Regency. The research lasted for 2 months from September to October 2023. The research was conducted in Radey Village, Tenga District, South Minahasa Regency. Data collection methods in this study were collected through primary data obtained through direct interviews with wet-rice farmers in Radey Village using questionnaires. Secondary data were taken from village and sub-district offices as well as previous research reports, journals, and from the internet related to the research. The sampling method was purposive sampling. The number of samples in this study were 20 respondents who owned farmland (owners) to determine priority risks. Data analysis used in this research is the FMEA (Failure Mode and Effect Analysis) method. Criteria in assessing risk refers to The Basic of FMEA by McDermott with a scale of 1 to 3. Calculate the priority level of each risk source based on the Risk Priority Number (RPN) value. The results showed that there are 2 sources of risk faced by rice farmers that are directly related to rice plants and affect rice farming, namely the risk of production risk sources and price and marketing risks, production risks as many as 4 risks, namely strong winds, pest and disease attacks, erratic weather and climate, high rainfall intensity. Price and marketing risks are 2 difficulties in the process of selling grain, and expensive fertilizer prices. Based on the calculation of the RPN (Risk Priority Number) value, there are 3 risks out of 6 risks faced by rice farmers that must be prioritized. The first risk that must be prioritized first is uncertain weather/climate with an RPN value of 14.25, the second risk of high rainfall intensity with an RPN value of 12.16, and the third risk of strong winds with an RPN value of 10.72.